Timothy of the cay - Taylor, Theodore 1921-2006 (Orlando : Scholastic, 1993)
Having survived being blinded and shipwrecked on a tiny Caribbean island with the old Black man Timothy, twelve-year-old white boy Phillip is rescued and hopes to regain his sight with an operation. Alternate chapters follow the life of Timothy from his days as a young cabin boy.
X
Sequel to: The cay.
860
X
Keywords: Shipwrecks -- Fiction; Survival -- Fiction; Black people -- Caribbean Area -- Fiction; Blind -- Fiction; People with disabilities -- Fiction